2016
DOI: 10.1007/s11605-016-3244-6
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Free Fluid on Computed Tomography: a Predictor of Surgical Intervention in Patients with Adhesive Small Bowel Obstruction

Abstract: High-density IFF on CT was significantly associated with the need for surgical intervention in patients with ASBO. Prospective study to validate the predictive value of high-density IFF on CT will be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…The mesenteric fluid sign results from venous congestion and transudation of fluid across serosa from mesenteric venous outflow obstruction; the absence of the mesenteric fluid sign decreases the probability of strangulation sixfold [59]. The presence of high-density intra-abdominal fluid (>10 Hounsfield units) on CT may predict the need for surgical intervention [72].…”
Section: Common Ct Signsmentioning
confidence: 99%
“…The mesenteric fluid sign results from venous congestion and transudation of fluid across serosa from mesenteric venous outflow obstruction; the absence of the mesenteric fluid sign decreases the probability of strangulation sixfold [59]. The presence of high-density intra-abdominal fluid (>10 Hounsfield units) on CT may predict the need for surgical intervention [72].…”
Section: Common Ct Signsmentioning
confidence: 99%
“…Previous studies have reported CT values of the exudative body fluids < 10 HU [ 17 ], while those of hemorrhagic peritoneal fluid range from 15 to 75 HU [ 18 ]. A recent study reported that CT values of peritoneal fluid > 10 HU in cases of SBO indicate the need for bowel resection [ 19 ]. It has been suggested that the greater the hemorrhage associated with the progression of II due to strangulation, the higher the CT values of free peritoneal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…En relación con los hallazgos tomográficos, existen conclusiones variadas. Al igual que en nuestro estudio, la presencia de líquido libre en otras series 17,19,24 se ha asociado con la necesidad de manejo quirúrgico, sobre todo en pacientes que presentan líquido libre de alta densidad 25 . Hwang, et al 26 , al igual que nosotros, reportan la zona de transición como un predictor de tratamiento quirúrgico.…”
Section: Discussionunclassified